Anália Franco e educação: trajetória, propostas e ações (1890-1919) - Lima, Juliana Maria da Silva Feijó de (2025)
This dissertation aims to give visibility to the trajectory, proposals, and actions of the educator and writer Anália Franco (1853-1919), presenting her as a pioneer of inclusive education in Brazil. The educator was an influential figure who developed strategies for the opening of her numerous educational, asylum, and charitable institutions, including the Beneficent and Instructive Women's Association of São Paulo (AFBISP/1903) and the Regenerative Colony D. Romualdo Seixas (1912), which aimed to serve what she called the "underprivileged classes", particularly children and women. In addition to working as a contributor to various periodicals, Anália Franco created her own vehicles for spreading her ideas: Álbum das Meninas (1898) and A Voz Maternal (1904), in which she defended the importance of education and work. These journals were documents used in the analysis, as well as other sources such as teaching materials and literary writings (focused on short stories) produced by Anália, as well as AFBISP reports, correspondence and a biography of the educator written by one of her students. Anália Franco dedicated her life to the struggle for education as a social reformer during the First Brazilian Republic, which is why this dissertation aims to analyze the motivations, path, actions, and writings of the educator, as well as retrieve her ideas about morality, based on her thought matrices – medicine, religion, and work – principles that shaped her practices and speech. As a writer, the educator belonged to a network of women and used the press as a tool to disseminate her ideas and literature as a form of representation and selfrepresentation, based on her experiences as references for building narratives, especially concerning the role of women as mothers and wives. In this sense, this dissertation presents Anália Franco in her different sides, as an emblematic figure who occupied spaces but acted through gaps and ruptures, in the search for changes regarding education, instruction, and female professionalization